Analysis of Mitigation Strategies against the Risk of Cost-Overrun during Implementation of Construction Projects - Martha Jaya, Nyoman; Gusti Ketut Sudipta, I; Dwi Meiarthini Suparta, Made (International Journal of Engineering and Technology, 2019)
Implementation of construction projects often experiences differences with field conditions planning. This discrepancy can be in the form of complexities and difficulties in the implementation of a construction project that can affect the increase in time and project costs. The cost that cannot be controlled in the implementation of construction project may cause a risk of cost overrun. This study aims to analyse the "mitigation strategy" against the risk of cost overruns in the implementation of construction projects. Data purposive responses were collected by survey method. After fulfilling statistical tests for questionnaire validity and data reliability, then a mitigation strategy analysis is continued against the risk of project cost overruns using the SWOT method (Strength, Weakness, Opportunity, and Threat). SWOT analysis shows "interaction" between internal factors (Strength and Weakness) with external factors (Opportunity and Threat). The amount of interaction weight indicates the priority of mitigation strategies between S-O (Strength-Opportunity), S-T (Strength-Threat), W-O (Weakness-Opportunity), and W-T (Weakness-Threat). The criteria for the value of each mitigation strategy are calculated from the smallest weight (1 is not important) to the largest (5 is very important). A calculation result of the S-O has the highest weight of 4.34. Thus, the implementation and improvement for the mitigation strategy of Strength-Opportunity (S-O) is a priority to overcome the risk of project cost overruns during the construction implementation stage.Â Â